Implementation of Administration In Providing Services To Students at MTS Nurul Muhajirin Tanjung Lago-Banyuasin - Kris Setyaningsih; Nurlaeli Nurlaeli; Mardeli Mardeli (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This article discusses the implementation of administrative Administration in providing services to students at MTs Nurul Muhajirin". This study aims to determine the implementation of administrative Administration in providing services to students at MTs Nurul Muhajirin. The type of research used in this research is qualitative research. Data were collected through observation, interviews, and documentation. This type of research approach is descriptive qualitative. The techniques used in data analysis are data reduction, data presentation, and conclusion. To test the research data's validity using technical and source triangulation. The results of this study indicate that the implementation of administrative Administration in providing services to students at MTs Nurul Muhajirin has been carried out well. These activities are related to the process of accepting new students, starting from planning admissions to implementing the process of accepting students and the announcement of new students. Other administrative activities, such as managing the ratio of students per class, are essential because the number of classes in a class will affect the student learning process. Furthermore, it relates to his duties, namely compiling and managing the condition of students in the madrasa. This was done for the sake of orderly Administration of students at MTs Nurul Muhajirin, and it has been done well. Then other activities, namely Administration, related to the overall assessment of the educational process at MTs Nurul Muhajirin Tanjung Lago.